Klimaschutz in finanzschwachen Kommunen. Potenziale für Haushaltsentlastungen, lokale Wertschöpfungseffekte sowie alternative Finanzierungsansätze kommunaler Klimaschutzmaßnahmen. - Heinbach, Katharina; Scheller, Henrik; Krone, Elisabeth; Reiß, Philipp; Rupp, Johannes; Walter, Jan; Altenburg, Corinna; Heinecke, Sabrina; Walker, Benedikt (My University, 2020)
Die Publikation führt die zentralen Ergebnisse unterschiedlicher Analysen aus dem Projekt "Zwischen Wertschöpfungseffekten und haushaltsrechtlichen Restriktionen: Qualifizierung finanzschwacher Kommunen zur Durchführung von Klimaschutzmaßnahmen (Quali-FiKo)" zusammen. Eingangs werden sowohl das rechtliche Verständnis des Begriffs "Finanzschwäche" - für den bisher keine bundesweit einheitliche Legaldefinition existiert - als auch die haushalts- und aufsichtsrechtlichen Rahmenbedingungen und Restriktionen von Kommunen bei der Durchführung von Klimaschutzmaßnahmen dargestellt. Auch werden die Herausforderungen beschrieben, denen finanzschwache Kommunen bei der Planung und Durchführung von Klimaschutzmaßnahmen begegnen. Im Weiteren gehen die Autorinnen und Autoren der Frage nach, welchen Mehrwert kommunale Klimaschutzaktivitäten zusätzlich zum primären Ziel - der Reduktion der Treibhaus-gasemissionen - für Kommunen haben können. Im Fokus stehen hier mögliche Kosteneinsparungen und das Potenzial für lokale Wertschöpfungs- und Beschäftigungseffekte. Zudem werden alternative Finanzierungsansätze jenseits der klassischen Finanzierung durch Kredite oder Förderprogramme von Bund und Ländern beschrieben, ihre Vor- und Nachteile dargestellt und ihre Eignung zur Finanzierung von Klimaschutzmaßnahmen finanzschwacher Kommunen bewertet.

In its Climate Action Plan 2050, Germany has set the goal to cut national greenhouse gas emissions by 40 percent until 2020 and by 80 to 95 percent until 2050, compared to 1990 levels. To reach these reduction targets, action is required at all political levels. Municipalities have a key role at this, as places of residence and business locations. However, climate action is still among the voluntary tasks of municipalities. Its execution is therefore highly dependent on human and financial resources of the respective city or municipality. This issue is a challenge particularly to financially weak municipalities, as they often struggle to balance their annual budget by own funds. In Germany, about 25 percent of all counties, cities and municipalities must follow specific budget. consolidation plans. Therefore, they are subject to severe restrictions when exercising both their mandatory and voluntary tasks. Tax revenue losses due to the corona virus outbreak are expected to further exacerbate the debt situation of many of these municipalities. Against this backdrop, the joint project "Between value added and budgetary restrictions: Qualifying financially weak municipalities for climate protection measures" aims to identify strategies to reduce existing budgetary and supervisory restrictions and to show alternative approaches to implement climate protection measures in financially weak municipalities. This publication conflates key results from different analyses within the project. First, a legal understanding of the term "financial weakness" - for which there is no uniform nationwide definition in Germany yet - is presented, as well as the budgetary and supervisory framework and restrictions that municipalities face when implementing climate protection measures. Those restrictions mostly result from the strained budgetary situation, but do go beyond that. Furthermore, the authors address the question of possible benefits from municipal climate protection activities - besides the primary goal of reduced green-house gas emissions. Here, they focus on cost savings as well as local value-added and employment effects. In addition, they present alternative financial instruments, including their advantages and disadvantages that exist, beyond classical approaches such as loans and funding schemes on the state and federal state level. This covers also an assessment of their applicability to fund climate protection measures in financially weak municipalities.
Keywords: Kommunaler Klimaschutz; Finanzkraft; Strukturschwäche; Wertschöpfung; Finanzierungsmöglichkeit; Haushaltsrecht; Aufsichtsrecht; Kommunalfinanzen; Gemeindefinanzhaushalt